Evaluation of operation synergy, optimal financing mix and dividend decision to maximize the value of business in inalum holding of mining - Tri Widodo, Ridho; Arif Sumirat, Erman (The Indonesian Journal of Business Administration, 2019)
Abstract. Introduction: Many strategic investments are often justified with the argument that they will create synergy. For holding mining establishment the goal was more on how to increase business capacity and funding, management of natural resources of mineral and coal, increase value added through downstream and increase local content, as well as cost efficiency through synergy. This paper aims to find the value of synergy in Inalum, PTBA, ANTM and TINS before establishment holding company of mining and the sensitivity the value to different assumptions and how to improve value of synergy in creating a holding company of mining. The major aims of mining holding company to create value and synergy in mining State-Owned Enterprises, with the expectation, it will increase revenue contribution to the country. These goals could be analyzed and measured by understanding of synergy based on two sources of synergies: operating synergy and financial synergy. This paper will assess operating synergy. Methods: In this valuation, Discounted Cash Flow (DCF) Framework will be used to recognize the potential source of synergy from operation. Results: This study found that gain from operation synergy of increasing growth and cost reduction will maximize the business value amounted USD 3,659,295.63, compared to gain from cost reduction USD -14,181,427.91  and gain from increasing growth USD 644,448.44. Conclusion: Given the results from study, it is important to derive the right strategy from investment decision to reflect the optimal source of synergy in order to maximize the business value in Inalum. Keywords:  DCF, investing decision, maximize business value, value of synergy